STRUKTUR KOMUNITAS FITOPLANKTON DI PELABUHAN JETTY PASCA KEGIATAN BONGKAR MUAT BATUBARA MEULABOH ACEH BARAT - MUNANDAR MUNANDAR MUNANDAR; YULI ERINA; MARZUKI MARZUKI (Journal of Aceh Aquatic Sciences, 2017)
This study aims to find out the structure of phytoplankton community in Jetty post-loading and unloading of coal, to know the abundance of phytoplankton, phytoplankton diversity index, and the dominance of phytoplankton species and to know the relevance of phytoplankton with physical and chemical parameters in the marine waters of Suak Indrapuri. This research was conducted on May-June 2017 which is located in the waters of Jetty port of Suak Indrapuri Meulaboh Village, Aceh Barat District. Research method used survey method with random sampling technique (simple random sampling). The results of identification of phytoplankton produced during the study found 8 species and 2 classes consisting of Chaetoceros curvisetus, Chaetoceros decipiens, Eucampia zoodiacus, Gyrosigma kutzingii, Rhizoselenia hebetata forma hiemalis, Thallasiothrix sp (Bacillariophyceae class) and Coscinodiscus sp, Skeletonema costatum (Coscinodiscophyceae class). The abundance of phytoplankton during the study ranged from 160-373 cells/l, said the abundance and spread of phytoplankton in the low-grade criteria. The phytoplankton diversity index during the study ranged from 1.775-1.925, which had the diversity and number of individuals of each type of medium phytoplankton, and the dominant index ranged from 0.55-1.566 the dominance of the species species of the phytoplankton medium was high. Measuring the quality of the marine waters of Indrapuri Suak with values varying between stations. Salinity is 15.2-38.2 ppt, the pH is relatively equal to the value of 7, Nitrate (NO3) 1.056-9.133 mg/l, temperature 25-27.4 0C, brightness 0.70-1.21 m, and current velocity 0.22-0.36 cm/sec. So the measuring value of seawater quality influences the life of phytoplankton organisms in the marine waters of Suak Indrapuri Meulaboh Aceh Barat.